Effect of eNOS on Ischemic Postconditioning-Induced Autophagy against Ischemia/Reperfusion Injury in Mice. (10th February 2019) - Shao, Jun; Miao, Chen; Geng, Zhi; Gu, Maohong; Wu, Yanhu; Li, Qingguo
Abstract : Autophagy is involved in the development of numerous illnesses, including ischemia/reperfusion (I/R). Endothelial nitric oxide synthase (eNOS) participates in the protective effects of ischemic postconditioning (IPostC). However, it remains unclear whether eNOS-mediated autophagy serves as a critical role in IPostC in the hearts of mice, in protecting against I/R injury. In the present study, the hearts of mice with left anterior descending coronary artery ligation were studied as I/R models. H9c2 cells underwent exposure to hypoxia/reoxygenation (H/R) and were examined as in vitro model. IPostC reduced mice myocardial infarct size and improved the structure of the heart. IPostC increased the formation of autophagosomes and increased the phosphorylation of eNOS and adenosine monophosphate-activated protein kinase (AMPK). Autophagy and eNOS inhibition suppressed the cardioprotective effects of IPostC. AMPK or eNOS inhibition abolished the improvement effect of IPostC on autophagy. AMPK inhibition decreased eNOS phosphorylation in the heart. Additionally, H9c2 cells suffering hypoxia were used as in vitro model. Autophagy or eNOS inhibition abolished the protective effects of hypoxic postconditioning (HPostC) against H/R injury. AMPK and eNOS inhibition/knockout decreased autophagic activity in the HPostC group. These results indicated that IPostC protects the heart against I/R injury, partially via promoting AMPK/eNOS-mediated autophagy.